Anti-Müllerian hormone as a marker of premature ovarian aging in autoimmune thyroid disease. (16th October 2014) - Saglam, Fatma; Onal, Eda Demir; Ersoy, Reyhan; Koca, Cemile; Ergin, Merve; Erel, Ozcan; Cakir, Bekir
Abstract: There is an increased incidence of autoimmune thyroid disease (AITD) in women with infertility. We hypothesized that serum anti-Müllerian hormone (AMH) levels will be lower in premenopausal women with AITD than controls. We evaluated ovarian reserve in women with AITD ( n  = 85) and healthy controls ( n  = 80), all <40 years old. Detailed data on reproductive history were obtained. Gonadotrophins, steroids, AMH, and inhibin B levels were measured during the follicular phase. The number of pregnancies as well as live births was lower in women with AITD ( p  < 0.01). No difference was observed in terms of FSH, estradiol, and inhibin B. AMH levels were lower in AITD women than in controls (1.16 + 0.17 versus 1.28 + 0.25 ng/ml, mean + SD, p  = 0.001). According to the multiple regression analysis, even after age adjustment, AITD was significantly and independently affected AMH levels ( t  = 2.674, p  = 0.008). Women with AITD seem to have a diminished ovarian follicular reserve and measurement of serum AMH level has the potential to be used to predict this comorbidity. Chinese abstract: 不孕女性群体中自身免疫性甲状腺疾病 (AITD)的发病率较高。我们假设，患自身免疫性甲状腺疾病的妇女的血清抗苗勒管激素比正常对照妇女的水平低。我们对85例AITD妇女和80例正常健康妇女的卵巢储备功能进行评估，年龄均小于40岁，记录详细的生育史数据。测量卵泡期的促性腺激素，类固醇，AMH，和抑制素B的水平。AITD群体的怀孕率和活产率均较低（p<0.01）。而FSH，雌二醇，和抑制素B水平没有明显差异。 AITD妇女的AMH水平比对照组水平低 (1.16 + 0.17 vs 1.28 + 0.25 ng/ml, 平均数±标准差, p < 0.001)。根据多重回归分析，即使经过年龄调整后，AITD显著地影响了AMH水平 (t=2.674, p=0.008)。AITD妇女似乎有较低的卵巢储备，检测AMH水平似乎可以预测此合并症。